Leonard Carmichael, with his wife standing to his left, being sworn-in at the Smithsonian Institution by Judge Harold Slepheus of the U.S. Court of Appeals, ca. 1938 - Smithsonian Institution (Tufts Archival Research Center, 2005)
8x10